Jewish and Armenian Population at the Base of Iasi County Development - Alexandra Georgiana Parasca (CES Working Papers, 2015)
Through this article I try to highlight the importance of Jewish and Armenian population which contributed to the development of Iasi County. They were a numerous population some centuries ago, contributing to commerce, being known as good merchants. Commerce was the base for establishing trade relations with foreign countries, therefore Armenians and Jewish helped in territorial and economic development of Iasi County. Also, they built churches, synagogues and schools for their community. Due to hard times, wars, discrimination, they had to leave the country for a better life, thus, their number decreased. As it is seen in the graphic and cartographic representations, the Jewish population decreased from 45,372 Jewish, in 1930, up to 257 Jewish, in 2011. As for the Armenian population, they decreased from 100 Armenian, in 1930, up to 14 Armenian, in 2011. Nowadays, they are not as numerous as they used to be, but they try to raise their visibility at local level through events on various occasions. I took into consideration the 1930-2011 censuses data from the National Institute of Statistics to observe the evolution of these two populations in Iasi County and how they diminished in time.
Keywords: Z12; Z13; 330; Jewish; Armenian; development; Iasi